Core and back rehabilitation for high-speed rotation sports: Highlight on lacrosse - Vincent, H. K.; Vincent, K. R. (Current Sports Medicine Reports, 2018)
Lacrosse is a fast-paced game that incorporates elements from multiple sports, such as soccer, basketball, baseball, tennis, and hockey. The sport involves rapid changes of direction, endurance, sprinting, physical contact, rotational movement, passing, and shooting. Passing and shooting are further complicated by having a weighted object (ball) at the end of a long moment arm (crosse) which places increased stress on the body segments. Thus, it is important to properly prepare for sport participation by improving strength, endurance, and dynamic stability of the postural and core stability muscles. Because high mechanical loads are experienced during play, (re)establishment of symmetric strength and flexibility is essential for rehabilitation and injury prevention. This article will focus on the musculoskeletal demands placed on the body in lacrosse, the importance of core strength and dynamic stability to prevent injury, and the elements of both prehabilitation and rehabilitation programs to properly prepare the athlete for participation.